Internationalizing the bachelor of quantity surveying programme at IIUM, a case study on students visit to Australia - Abdul Rashid, Khairuddin (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2005)
A group of fourth (final) year students of the Bachelor of Quantity Surveying (Honours) Programme at the International Islamic University Malaysia (HUM) visited Adelaide Australia in July 2003. The visit represented part of a course entitled International Construction Procurement. The course aims at providing the students with first hand knowledge and exposure on construction procurement in an international context and is offered in line with IIUM's mission to incorporate international elements into learning and teaching. The paper outlines the course contents, preparations and constraints encountered while carrying out the study visit and reports key observations made by the students. The paper concludes by summarizing the benefits gained by the students and IIUM from the study-visit and the course as a whole.